Study of the influence of the foundation and the reservoir on the dynamic response in a concrete gravity dam profile - Silveira,Iarly Vanderlei da (2021)
abstract: This work aims to verify the influence of the foundation and the reservoir on the dynamic behavior of concrete gravity dams in terms of the natural frequencies, vibration modes for a free vibration analysis; and in terms of maximum displacements and maximum stresses at singular points of the structure for a seismic excitation. The dam-reservoir-foundation interaction was investigated through modal and transient analysis by the finite element method via ANSYS APDL software. For this study, we used a typical Brazilian dam profile and compatible data from a Brazilian earthquake for the seismic excitation. The results showed the influence of the reservoir and the foundation on the natural frequencies in the coupled system, as well as its repercussions on the response of the dam under seismic excitation.